Efek Skarifikasi Air Panas Dengan Variasi Suhu Dan Waktu Pada Perkecambahan Biji Kacang Hijau (Vigna radiata L.) - Setiyanto, Afif Eka Rahma; Munawarti, Aminatun (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to analyze the effect of initial temperature variation and hot water scarification time on the germination of mung bean seeds. Seeds measuring 0.2 ± 0.05 cm in size and dark green in color were scarified using various scarification treatments, namely control (without scarification) (P0), room temperature for 10 minutes (P1), room temperature for 60 minutes (P2), 35°C for 10 minutes (P3), 35°C for 60 minutes (P4), and 55°C for 10 minutes (P5), with a germination period of seven days. The experimental design used was a completely randomized design with four replications, each replication using 25 seeds. The parameters observed were germination percentage, germination rate index, germination rate, radicle length, and plumule length. The best germination percentage and germination speed index were produced by the control (P<0.05). The best germination rate was produced by the P3 temperature treatment. Radicle length and plumule length did not differ significantly (P<0.05) across all treatments. Hot water scarification with varying temperatures and times in this study did not induce better mung bean germination than the control.